Building bio-innovation systems through advanced biotechnology education - Cardozo Ruíz Díaz, Edgar; Quintana, Silverio Andrés; Rojas, Cinthia Mabel; Fernández Ríos, Danilo (Frontiers in Bioengineering and Biotechnology, 2024)
We discuss the role of advanced biotechnology education in fostering sustainable bio-innovation systems. As a case study, we focus on Paraguay's Graduate Diploma in Innovation Management and Biotechnological Projects, which emphasizes interdisciplinary collaboration, stakeholder integration, and professionals skilled in the interplay between biotechnology, society, and governance. We highlight the relevance of educational programs in addressing the gap between academic research and industrial needs, thereby contributing to the sustainable growth of the biotechnology sector.